PENGEMBANGAN PERANGKAT PEMBELAJARAN MATEMATIKA BERBASIS KURIKULUM 2013 DENGAN MODEL PENEMUAN TERBIMBING PADA MATERI LINGKARAN UNTUK PESERTA DIDIK KELAS VIII SMP/MTs - W. Eggy Yufentya; Titi Solfitri; Syarifah Nur Siregar (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The background of this study is the restrict of mathematic learning instruments as supporting learning referring to Curriculum 2013. This study aimed to develop mathematics learning instruments with guided discovery model on circle’s topic for 8th grade SMP/MTs. Learning instruments which will be developed in this study are syllabus, lesson plans, and student worksheet. This study method used is ADDIE model by Dick and Carey that consist of analysis, design, development, implementation and evaluation. Test instruments that used in this study are validation instrument that is validation sheets to evaluate the advisability of syllabus, lesson plans and student worksheet and then practicality instrument that is questionnaire which will be filled up by students to evaluate practicality of student worksheet. Learning instruments that has been developed is being validated by three validators and being tested in a small test group consist of five on June 9th–10th, 2016 in SMPN 1 Pekanbaru for student worksheet. Based on the data analysis, it can be conclude that mathematics learning instruments is very valid with mean score of syllabus is 4,49, for lesson plans is 4,31, and for student worksheet is 4,22. This student worksheet also valued as very practical with mean percentage of student responses is 4,87 with 97%.Key Word: Mathematics Learning Instrument, Guided Discovery Model, Research andDevelopment, ADDIE Model